My Story - Gerrard, Steven, author; McRae, Donald, author (London : PENGUIN BOOKS, 2016)
In My Story, Gerrard speaks fully and frankly about his extraordinary playing career, opening up about the key matches and moments to give readers the view from on the pitch. His exhilarating accounts of winning and losing while staying loyal to one club through good and bad tell us about his commitment both to the game and to Liverpool. It's a story of a deeply personal relationship between one man, his club and the fans.